ANALISIS IMPLEMENTASI AKAD PADA REKSADANA SYARIAH MANULIFE SYARIAH SEKTORAL AMANAH KELAS A - Saqina Putri, Zharfa Athirah; Putri, Erisha; Romansza, Raihan Falqahi; Wiryanto, Fadhli Suko (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2022)
Sharia mutual funds are one of the halal investment options because they are in accordance with sharia provisions. In this sharia mutual fund, wakalah and mudharabah contracts are used. The contract between the investor and the investment manager uses a wakalah contract. Meanwhile, the contract between the investment manager and the investment user uses a mudharabah contract. This study aims to analyze the implementation of contracts in Reksadana Manulife Syariah Sektoral Amanah Kelas A. The research method used is a literature study by reviewing several journals and literature related to the topic of discussion. From the results of the analysis, it is shown that the Reksadana Manulife Syariah Sektoral Amanah Kelas A rights and obligations between investors as owners of capital and investment managers as users of capital are regulated using wakalah and mudharabah contracts. This sharia mutual fund complies with sharia provisions and is halal to be used as an investment. By looking at the development of sharia mutual funds in Indonesia, the author would like to analyze and provide deeper insight into the implementation of the contracts used in sharia mutual funds in Indonesia, especially in the Manulife Syariah Sektoral Amanah Kelas A Mutual Funds.